Observability of Isolated Stellar-mass Black Holes - Lena Murchikova; Kailash C. Sahu (The Astrophysical Journal Letters, 2025)
Stellar-mass black holes (BHs) represent the natural end states of massive stars. It is estimated that 10 ^8 stellar-mass BHs are present in the Milky Way galaxy, a significant fraction of which are expected to be isolated. Despite their expected abundance, only about 20 have been detected so far—mostly in binary systems—with just one confirmed isolated black hole (IsoBH) identified via astrometric microlensing. In this study, we investigate the potential for detecting electromagnetic emissions from IsoBHs by generating synthetic model spectra of their emissions in different types of interstellar medium environments. These model spectra are then compared with current observational capabilities. We show that photons emitted by IsoBHs—especially those accreting material in dense environments or within the solar neighborhood—should be readily detectable. However, confidently identifying these sources remains highly challenging. We conclude that a number of IsoBHs must already exist in current astronomical catalogs but have not been identified as such. We outline possible strategies for the detection and identification of IsoBHs using the current and upcoming telescopes.